Global and regional estimates of preeclampsia and eclampsia: a systematic review - Abalos, Edgardo; Cuesta, Cristina; Grosso, Ana L.; Chou, Doris; Say, Lale (European journal of obstetrics & gynecology and reproductive biology, 2013)
Reduction of maternal mortality is a target within the Millennium Development Goals. Data on the incidence of preeclampsia and eclampsia, one of the main causes of maternal deaths, are required at both national and regional levels to inform policies. We conducted a systematic review of the incidence of hypertensive disorders of pregnancy (HDP) with the objective of evaluating its magnitude globally and in different regions and settings. We selected studies using pre-specified criteria, recorded database characteristics and assessed methodological quality of the eligible studies reporting incidence of any HDP during the period 2002–2010. A logistic model was then developed to estimate the global and regional incidence of HDP using pre-specified predictor variables where empiric data were not available. We found 129 studies meeting the inclusion criteria, from which 74 reports with 78 datasets reporting HDP were analysed. This represents nearly 39 million women from 40 countries. When the model was applied, the overall estimates are 4.6% (95% uncertainty range 2.7–8.2), and 1.4% (95% uncertainty range 1.0–2.0) of all deliveries for preeclampsia and eclampsia respectively, with a wide variation across regions. The figures we obtained give a general idea of the magnitude of the problem and suggest that some regional variations might exist. The absence of data in many countries is of concern, however, and efforts should be made to implement data collection and reporting for substantial statistics. The implementation of large scale surveys conducted during a short period of time could provide more reliable and up-to-date estimations to inform policy.